VD_FINDINFO Jug / 2022 / 477 vom 8. September 2022 - VD Tribunal cantonal (2022)
FAUTE GRAVE, DILIGENCE, CERTIFICAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, JUSTE MOTIF | 321a CO, 330a CO, 337 CO, 47 LPers-VD, 61 LPers-VD, 113 RLPers-VD